Business Process Reengineering pada Reservasi Pasien Rumah Sakit Umum Universitas Muhammadiyah Malang - Ikhsanul Putra; Ilyas Nuryasin (Universitas Muhammadiyah Riau, 2024)
As a healthcare institution, Universitas Muhammadiyah Malang General Hospital is in need of improvement in operational efficiency, easy access to information, and good service to patients and prospective patients. The General Hospital of Universitas Muhammadiyah Malang still has an inefficient process for registering patients, as the registration machine provided by the hospital is limited and can only be used by patients who come to the hospital. This causes long queues when a large number of patients register. Another problem is that some of the information related to the reservation process is only available directly at the hospital, which causes potential patients to return on another day when the clinic or department they want to go to is not available. Business Process Reengineering (BPR) is one of the solutions that can be done on the problems encountered in patient reservations at UMM Hospital. In conducting BPR, business processes can be eliminated or optimized to improve the efficiency of the process. This research conducts BPR using ASME (American Society of Mechanical Engineers) standards and throughput efficiency tests as a tool to measure the efficiency of new and old business processes. In this study, the throughput efficiency results of the initial business process in the patient reservation process of the General Hospital of Muhammadiyah University of Malang amounted to 49.09% and increased to 97.38% in the recommended business process after business process reengineering. Furthermore, the advantages and disadvantages were analyzed to find out the problems that may occur in the results of the recommended business process. The final result of this research is a solution in the form of a mobile application interface design that has been adapted to the needs based on the recommended business process.